2008
DOI: 10.1007/s00023-008-0369-5
|View full text |Cite
|
Sign up to set email alerts
|

Poisson Statistics of Eigenvalues in the Hierarchical Anderson Model

Abstract: We study the eigenvalue statistics for the hieracharchial Anderson model of Molchanov [21][22][23]27,28]. We prove Poisson fluctuations at arbitrary disorder, when the the model has a spectral dimension d < 1. The proof is based on Minami's technique [25] and we give an elementary exposition of the probabilistic arguments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 27 publications
0
57
0
1
Order By: Relevance
“…The Dyson hierarchical ferromagnetic Ising model [60] has been much studied by both mathematicians [61][62][63][64] and physicists [65][66][67][68][69]. More recently, various Dyson hierarchical versions of disordered systems have been considered, in particular Anderson localization models [72][73][74][75][76][77][78][79], random fields Ising models [70,71] and spin-glasses [80][81][82][83][84].…”
Section: B Related Dyson Hierarchical Spin-glassmentioning
confidence: 99%
“…The Dyson hierarchical ferromagnetic Ising model [60] has been much studied by both mathematicians [61][62][63][64] and physicists [65][66][67][68][69]. More recently, various Dyson hierarchical versions of disordered systems have been considered, in particular Anderson localization models [72][73][74][75][76][77][78][79], random fields Ising models [70,71] and spin-glasses [80][81][82][83][84].…”
Section: B Related Dyson Hierarchical Spin-glassmentioning
confidence: 99%
“…Therefore, close to the upper spectral edge E pure ∞ , the integrated DOS exhibits the asymptotic behaviour 8,12,14,15 …”
Section: -23mentioning
confidence: 97%
“…Contrary to the rigorous results established for the density of states (DOS), 8,[12][13][14][15] less work has been devoted to the study of the nature of the eigenstates of the HAM. In a recent paper, 16 the authors have shown the existence of an extended phase for a sufficiently slow decay of the hopping energy, in contrast to a previous conjecture stating that all states should be localized.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, the first proof of complete spectral localization for the hierarchical model at any c > 0 in the special case of a Cauchy probability density is due to S. Molchanov [26]. Later, E. Kritchevski showed [18,20] that H almost surely has only pure-point spectrum provided that either V has a Cauchy component or c > 1/2 and that the rescaled eigenvalues converge to a Poisson point process if c > 2. Proposition 2.2 gets rid of any conditions on the distribution or the spectral dimension and may be considered optimal as far as spectral localization is concerned.…”
Section: Theorem 24 (Poisson Statistics) Suppose Assumption 11 Is mentioning
confidence: 99%
“…The first proof of complete spectral localization for the hierarchical model in the special case of a Cauchy random potential of arbitrary strength is due to S. Molchanov [26]. His proof ideas where later extended to more general distributions by E. Kritchevski [18,20]. Notably, neither of these works proved or even conjectured the appearance of a delocalized phase in the regime of longrange, but summable hopping strength of the hierarchical Laplacian.…”
Section: Introductionmentioning
confidence: 99%